Reversibility and reproducibility of histamine induced plasma leakage in nasal airways - Svensson, C; Baumgarten, C R; Pipkorn, U; Alkner, U; Persson, C G (Thorax, 1989)
Plasma exudation is one cardinal factor in airways defence and inflammation. In inflammatory airway diseases such as rhinitis and asthma, however, plasma leakage may also have a pathogenetic role. Experimental data from animals indicate that highly sensitive, active, and reversible processes regulate the vascular and mucosal permeability to macromolecules. With the use of a nasal lavage model for the recovery of liquids on the mucosal surface the effect of histamine on the macromolecular permeability of the airway endothelial-epithelial barriers was studied in normal subjects. The concentrations of albumin, kinins, and N-alpha-beta-tosyl-L-arginine-methyl esterase (TAME) in nasal lavage fluid were measured and nasal symptoms assessed by a scoring technique. The reproducibility of three repeated challenges with 30 minute intervals on the same day was studied in 12 subjects and compared with the same procedure (three challenges) on a different day. Sneezing decreased significantly (p less than 0.05) after the first histamine challenge but was maintained thereafter. Otherwise, the mean values for symptoms and for markers of vascular leakage were very similar both for the three challenges in the same session and for the two challenge sessions on a different day. Sneezing, blockage, and secretions were associated with increased concentrations of TAME esterase (maximum 9000 cpm/ml), kinins (1.4 ng/ml), and albumin (0.3 g/l) in lavage fluid. Both the symptoms and the measures of plasma exudation were reversible and reproducible in the three repeat histamine challenges and at two challenge sessions on different days. These findings support the view that non-injurious, active processes regulate the inflammatory flow of macromolecules across airways endothelial-epithelial barriers. The present experimental approach would be suitable for studies of the modulatory effects of inflammatory stimulus induced plasma leakage and symptoms in human airways.